Cerita Rakyat “Saliwu, Pahlawan Suku Padoe” - nfn Mustafa (Balai Bahasa Provinsi Riau, 2018)
This study aims to research Luwu's oral literary work on the character of the story based on the Levi-Strauss analysis model.